EMPATI DAN GENUITAS DALAM POLITIK INDONESIA: MENEMUKAN KEMBALI “HATI” YANG HILANG - raga, Yohanes Dopo; Pemo, Patrisius (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2026)
This paper aims to analyze and examine the phenomenon of the loss of conscience and genuineness in political practice in Indonesia. The main problem studied is the decline in the values ​​of empathy and authenticity of political leaders, which has resulted in a loss of public trust in the government and a breakdown in the relationship between the people and leaders. This study uses a qualitative method with a library approach to examine theoretical concepts and empirical phenomena related to empathy, political leadership, and public trust. The results show that a deficit of empathy in political decision-making tends to produce deviant policies that fail to address the needs of the people, while the loss of genuineness creates a crisis of public trust in the government. Political rhetoric that is more oriented towards public image is a major factor in this. Therefore, it can be concluded that the loss of the dimensions of conscience and genuineness in leadership has created a crisis of public trust in the political situation in Indonesia. Therefore, efforts to restore public trust need to be intensified by reviving the values ​​of empathy and authenticity in political practice, so that politics can again become an instrument to serve and improve the welfare of the people, rather than being used as a tool to maintain power.